Asosiasi Antara Kemampuan Analogi Dengan Komunikasi Matematik Siswa SMP - Azmi, Memen Permata (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
This research is a quantitative research with cross-sectional design that aims to examine the association between students 'mathematical analogy abilities with students' mathematical communication abilities. The subject of this research is 33 students of class VII in one of Junior High School of Kampar Regency of Riau Province. The instrument used is a essay test about the problem of mathematical analogy and mathematical communication. Data analysis techniques to test the association of both capabilities based on the category of contingency association test (Pearson Chi Square test and contingency coefficient). The results showed that this study was an association between students' mathematical analogy abilities with students' mathematical communication abilities. The degree of association between students 'mathematical analogy abilities with students 'mathematical communication abilities is high.